Robotic-Assisted Laparoscopic Prostatectomy for High-Risk Prostate Cancer: Technical Considerations and Review of the Literature. (25th September 2011) - Stroup, Sean P.; Kane, Christopher J.
Abstract : Men with high-risk prostate cancer are at significant risk of progressive, symptomatic disease leading to metastases or death from prostate cancer. Surgery—specifically robotic-assisted laparoscopic prostatectomy (RALP)—is increasingly being considered as a key component of a multimodal strategy to treat these patients. Herein, we review key technical considerations of performing RALP with bilateral pelvic lymphadenectomy in men with high-risk disease. Recent literature supporting the increasing role of surgery either alone or in combination with adjuvant therapies to treat men with high-risk prostate cancer is also reviewed.